CARDIORESPIRATORY RESPONSE TO AEROBIC EXERCISE WITH NONINVASIVE VENTILATION IN THE COPD PATIENTS (Fiep Bulletin - online, 2012)
Introduction: Patients with Chronic Obstructive Pulmonary Disease (COPD) have submitted losses in the ability to exercise and the use of non-invasive ventilation (NIV) associated with aerobic exercise improves tolerance to effort in these patients. Objective: To evaluate the cardiorespiratory response to aerobic exercise on a ergometer cycle with the use of NIV in COPD patients. Methods: the Case study investigated 08 patients of both sexes, submitted to aerobic exercise on a cycle ergometer with and without the use of NIV (Bi-Level Positive Airway Pressure BiPAP and Continuous positive airway pressure, CPAP). The variables analyzed before, during and after from the exercise recovery to  the resting values ??were: blood pressure (BP), heart rate (HR), oxygen saturation (SpO2), the Borg Dyspnea Scale (EBD) and Perceived exertion (EBEP). Results: There was a significant difference between men and women for SBP and DBP at rest without NIV [SBP (men vs. women 130 ± 113 8.16 ± 5.00, p = 0.01) and DBP (men 83 ± 5, women 00 vs. 73 ± 5.00, p = 0.03)]. The score in EBEP was lower in women with CPAP (8.5) and men with BiPAP (09), compared to spontaneous breathing (9.5). The score was lower in the CPAP EBD (01) and BiPAP (0) for both groups, compared to spontaneous breathing. The recovery of HR at rest was prolonged with the use of NIV in men and dyspnea at rest was a relevant factor for the extension of this time. Conclusion: The use of NIV improved respiratory performance of COPD patients in this study, with the absence of dyspnea during aerobic exercise.
Keywords: Cardiorespiratory Response; COPD; Exercise Tolerance. Non-Invasive Ventilation (NIV); Cardiorespiratory Response. COPD. Exercise Tolerance; Non-Invasive Ventilation (NIV).